Tinggal dan Berbuah di Dalam Yesus: Eksegesis terhadap Yohanes 15:4-5 - Daniel Horatius Herman (Predica Verbum: Jurnal Teologi dan Misi, 2021)
There are many interpretations made of John 15: 4-6. The many interpretations can lead to confusion about the purpose of Jesus. This study aims to find the meaning of the teachings of Jesus according to Jesus' intent so that the problems of different interpretations can be resolve. This study was done by exegeting and relating the text to the context of Jesus' story, the context of the Gospel of John, the context of the Old Testament, and the context of the first reader and then implies its meaning to current Bible readers. This research was conduct in three parts. First, study 15:4 “Abiding versus Not Abiding in Jesus.” which refers to a command or invitation to take sides with Jesus; The second study on 15: 5 Fruitful versus Unfruitful. It relates directly to the responses to the invitation in the first section; and third, the study of 15: 6 He threw out, He dried and is on burning. This section describes the condemnation of rejecting Jesus.